OUTLOOK REGIONAL DEVELOPMENT WITH THE OPERATION OF IRON IN RESERVES CAETITÉ COUNTY, BAHIA - Pontes, Bethania Maria Santos (2015)
Brazil is globally regarded as a potential producer of iron ore. Deposits known and explored the states of Minas Gerais, Pará and Mato Grosso do Sul hold approximately 99% of the reserves. In recent years the increasing demand for mineral deposits led to new researchers in the municipality of Caetité, south-central region of Bahia. The project implementation for the operation and logistics for the marketing of the product will generate taxes and moving the local and regional economy, bringing the state to the third largest producer of iron ore in the country. The hinterland to the coast, changes in landscape aspects, environmental and socioeconomic become part of the scenery Bahia, due to the insertion of the district ferriferous.